THE FIRST LABOUR LAW NUMBERED 3008 IN THE PARLIAMENT FORMAL REPORT ON JUNE 8, 1936: ELIMINATING LIBERALISM AND REPLACING STATISM - Hasan YÜKSEL (Fırat University, 2019)
The objective of the study is to analyze the first labour law accepted on June, 1936 and put into practice on 15 June, 1936 by promulgating moving from the parliament formal reports and in this context, to reveal the general peculiarities of the law on the basis of “liberalism and statism” which is laid an emphasis in the first Labour Law of Turkish Republic. As known, 1930s of Turkish Republic reflect the era that includes the elimination of the liberal oriented policies and that attached importance to centered policies. Within the context of decisions taken in İzmir Economy Congress in 1923, the period between 1923 and 1930 was shaped by the liberal oriented policies, however, the economic crisis caused by Great Depression occurred in 1929 forced the countries to shift their economic policies and new era that included the intervention of the states to the market economy commenced. In coordination with the world itself, via government business enterprises founded after 1934, Turkey adopted the idea of “minimum capital, maximum state” Particularly, capital accumulation is tried to be provided through state instead of private initiatives. The effective role of state in the accumulation of capital can be seen in the new law passed in the country and in this framework, in the first law and the first labour law numbered 3008 passed in the aftermath of 1934, liberal state was criticized and work life organized through state was given priority. The study consists of three parts. In the first part of the study, the Law and the regulations that shaped the labour life before the Republican Period was ascertained, in the second chapter of the study, the Laws passed after the Republican period was emphasized. Moreover, the first six years of Turkish Republic that encompass 1923-1930 and that was given a shape with liberalism and later on the transfer to state based economy commenced with government business enterprises was studied. As for the last part of the study, liberalism and statism in the formal parliament reports on June 8, 1936 were analyzed.